The English novel and prose narrative - Amigoni, David (Edinburgh : Edinburgh University Press, 2000)
"The English Novel and Prose Narrative provides an astute, wide-ranging and accessible critical introduction to the English novel and short fiction, and explores the novel's relations to narrative forms such as biography and autobiography. David Amigoni expertly guides readers to methods of narrative analysis and close reading, while stressing the need to place narrative and narrative theories in historical and cultural context. To this end, he traces critical debates about the origins of the novel, domestic realism and romance, the bildungsroman, journalism and mass culture, the experimental novel, postmodernism and postcolonialism." "Adopting a case-study approach, the author provides theoretically informed readings of Pamela Tristram Shandy, Emma, Jane Eyre, The Mill on the Floss, Bleak House, The Spoils of Poynton, Mrs. Dalloway and Midnight's Children as well as short stories by Thomas Hardy and Katherine Mansfield. While primarily an introductory guide, the book also offers a distinct approach to the history of novel criticism that will engage readers interested in the genre at the levels."--Jacket
1. Introduction: straightforward discourse and novel transactions -- 2. elements of narrative analysis and the origins of the novel: reading Jane Austen's Emma and Samuel Richardson's Pamela -- 3. Bildung and belonging: studying nineteenth-century narrative and 'self-culture' -- 4. Innovative stories and distinctive readers -- 5. History, intertextuality and the carnivalised novel: postmodern conditions and postcolonial hybridities.
Print version record.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: English fiction -- History and criticism; English prose literature -- History and criticism; Narration (Rhetoric); English; Languages & Literatures; English Literature; Roman anglais -- Histoire et critique; Prose anglaise -- Histoire et critique; Narration; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- General; English fiction; English prose literature; Narration (Rhetoric); Fictie; Engels; Criticism, interpretation, etc